2019
DOI: 10.1007/s10551-019-04261-1
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Authoritarian Leadership on Ethical Voice: A Moderated Mediation Model of Felt Uncertainty and Leader Benevolence

Abstract: In a sample of 522 police officers and staff in an English police force, we investigated the role of authoritarian leadership in reducing the levels of employee ethical voice (i.e. employees discussing and speaking out opinions against unethical issues in the workplace). Drawing upon uncertainty management theory, we found that authoritarian leadership was negatively related to employee ethical voice through increased levels of felt uncertainty, when the effects of a motivational-based mechanism suggested by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 83 publications
8
93
0
1
Order By: Relevance
“…The results revealed that the four-factor measurement model had a good fit ( Table 2 ), i.e., χ 2 = 196.05, χ 2 /df = 1.74, CFI (Comparative Fit Index) = 0.90, TLI (Tucker-Lewis Index) = 0.87, RMSEA (Root Mean Square Error of Approximation) = 0.07, and SRMR (Standardized Root Mean Square Residual) = 0.07, as compared with other alternative models. Although the hypothesis model had a relatively low TLI value, as suggested by Zheng et al [ 71 ], the observed items had significant loadings on their respective latent factors, supporting the measurements used in this study. Second, we utilized SPSS software v19.0 (IBM, Almaden, CA, USA) to conduct Herman’s single factor test on the survey data.…”
Section: Resultssupporting
confidence: 84%
“…The results revealed that the four-factor measurement model had a good fit ( Table 2 ), i.e., χ 2 = 196.05, χ 2 /df = 1.74, CFI (Comparative Fit Index) = 0.90, TLI (Tucker-Lewis Index) = 0.87, RMSEA (Root Mean Square Error of Approximation) = 0.07, and SRMR (Standardized Root Mean Square Residual) = 0.07, as compared with other alternative models. Although the hypothesis model had a relatively low TLI value, as suggested by Zheng et al [ 71 ], the observed items had significant loadings on their respective latent factors, supporting the measurements used in this study. Second, we utilized SPSS software v19.0 (IBM, Almaden, CA, USA) to conduct Herman’s single factor test on the survey data.…”
Section: Resultssupporting
confidence: 84%
“…Ethical voice. Ethical voice was measured by a four-item scale (Zheng, Graham, Farh, & Huang, 2019), adapted from Tucker, Chmiel, Turner, Hershcovis, and Stride's ( 2008) safety voice measure. We used this measure because it specifically focuses on voice targeted at colleagues, such as "telling a colleague who is doing something unsafe to stop."…”
Section: Ethical Value Internalizationmentioning
confidence: 99%
“…Perceived uncertainty of management style was assessed with a three-item scale developed by Thau et al (2009) . The sample item was “I find management’s actions and decisions unpredictable.” Moreover, leader busyness reflects that the leader has a lot of work to do, which is related to the effectiveness of leaders ( Zheng Y. et al, 2019 ). We propose that perceived leader busyness positively relates to perceived leadership effectiveness.…”
Section: Study One: Scale Development and Validationmentioning
confidence: 99%
“…When followers convey limited and vague information, leaders may find it difficult to accurately understand the work status of followers ( Brown et al, 2015 ). At the same time, leaders may misinterpret limited information of followers as challenging—or disrespectful ( Mead and Maner, 2012 ; Zheng Y. et al, 2019 ), which may lead to negative evaluations for followers. To capture the full picture of leaders’ evaluation of followers, we focus on leaders’ task performance evaluation, conscientiousness behavior evaluation, and counterproductive behavior evaluation of followers.…”
Section: Introductionmentioning
confidence: 99%